The Effect of Yoga on Body Mass Index and Dysmenorrhoea in Female Students Majoring - Rahmayani, Devi; Anshori, Jamil; Satriani, Satriani (Nutrition Study Program, Faculty of Medicine, Universitas Negeri Semarang, Indonesia, 2024)
Introduction: Dysmenorrhoea is pain that occurs during menstruation. This causes the body to feel bad and reduces the routine activities of people with dysmenorrhoea. One factor that can reduce dysmenorrhoea is yoga exercises. Yoga is a physical activity, learning mental and breathing techniques to relieve stress, relieve anxiety, reduce menstrual pain, and control weight to be more ideal. This study aims to determine the effect of yoga on body mass index and dysmenorrhoea in female students of the Department of Nutrition at the Ministry of Health East Kalimantan Polytechnic. Method: This research is a type of Experimental Quasy research with a type design of group pretest-posttest design. This research was carried out at the nutrition building of the Ministry of Health East Kalimantan Polytechnic in March-April. The samples used were 14 female students majoring in nutrition using a simple random sampling technique. This research has met the ethical requirements and is approved to be carried out, taking into account the National Health Research and Development Ethical Guidelines and Standards (PSEPPKN) with certificate number DP.04.03/7.1/7844/2023. Bivariate analysis is carried out to determine whether there is an influence between each variable using the Wilcoxon test. Results: The results of this study showed the influence of yoga on body mass index and dysmenorrhoea in female students majoring in nutrition at the Ministry of Health East Kalimantan Polytechnic marked by p-value Body mass index 0.019 < 0.05 and P-Value dysmenorrhoea 0.000 < 0.05. Conclusion: Yoga significantly influences body mass index and dysmenorrhoea in female students majoring in nutrition at the Ministry of Health East Kalimantan Polytechnic. Suggestion: This can be used as an essential reference for similar research on the effect of yoga on body mass index and dysmenorrhoea and covers a wide range of respondents.